2010
DOI: 10.1016/j.schres.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and associated factors in older adults with schizophrenia

Abstract: Background Although there have been numerous studies of suicidality in younger populations with schizophrenia, there have been no studies focused on community-dwelling older adults with schizophrenia. This study provides data on the prevalence of suicidality and factors associated with previous suicide attempts among a mixed racial sample of older persons with schizophrenia living in New York City. Methods The schizophrenia group consisted of 198 persons aged ≥55 years who developed schizophrenia before age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…We found that EA and PA were associated with suicidal behavior, which was consistent with a study conducted in Western countries (Cohen et al, 2010). In contrast, PA, EN, PN and total abuse were significantly related to aggressive behavior in this sample, which is consistent with findings reported by another study conducted in Chinese schizophrenic samples (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that EA and PA were associated with suicidal behavior, which was consistent with a study conducted in Western countries (Cohen et al, 2010). In contrast, PA, EN, PN and total abuse were significantly related to aggressive behavior in this sample, which is consistent with findings reported by another study conducted in Chinese schizophrenic samples (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…A rapidly growing body of literature is examining the impact of childhood trauma on various clinical features and symptoms particularly post-traumatic stress disorder (PTSD) symptoms in individuals with schizophrenia and other serious mental illnesses (Calhoun et al, 2007;Gearon et al, 2003;Lysaker et al, 2001;Rosenberg et al, 2007). However, very few studies have focused on the effect of childhood trauma on suicidal and aggressive behaviors in patients with schizophrenia (Cohen et al, 2010). The dose-effect of childhood trauma on clinical features also remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen et al (20) found a 4 % increase in current suicidality and a 26 % -49 % increase in lifetime suicidality among older schizophrenic patients (aged 55 years and older) in NYC when compared with a community control group. While a NYC based study was not found for younger persons with schizophrenia, meta-analyses suggest that suicide rates in adolescents and young adults with schizophrenia have been found to be up to three times higher than rates in older populations (24) .…”
Section: Suicide In New York Citymentioning
confidence: 98%
“…Owing to the recent increase in PTSD symptomology in Manhattan following the September 11th terrorist attacks and the wars in Iraq and Afghanistan, it is important for clinicians and general health professionals to be aware of the associations between PTSD and suicidality (14,20,22) .…”
Section: Suicide In New York Citymentioning
confidence: 99%
“…Sadly,theriskofsuicideforpersonsexperiencingschizophrenia ishigherthanforotherdiagnosticgroups.Thedistressassociated withthedisorderresultsin40%-50%ofthosepersonsexperiencing suicidalideationduringtheirlifetimes,with20%-50%attempt-ingtheactand5%-10%succeeding (Banwari,Vankar,&Parikh, 2013;Kasckow,Felmet,&Zisook,2011).Ratesareloweramong personswhousethenewerantipsychoticdrugs,possiblybecause oftheirreducedriskofadverseeffects(Reutforsetal.,2013).The risk of suicide attempts is greatest during the first 10 years after the onset of the disorder, with 50% occurring during the first 2 years. Even into middle age (after 45 years old), however, 24% ofpersonwithschizophreniaexperiencesuicidalideationand5% make attempts (Cohen, Abdallah, & Diwan, 2010).Those with accompanyingmooddisordersareatthreetimestheriskofothers (Reutforsetal.,2010).…”
mentioning
confidence: 99%